Psoriasis Severity and the Prevalence of Major Medical Comorbidity and the Effectiveness of Diagnostic Imaging of Psoriatic: A Population-Based Study Among Adult Patient Kingdom of Saudi Arabia 2021 - Salem Hammad Muslh , Rasha Saeed Alghamdi , Mohammed Ali Almahhan Aldwues , Mesharl Marzouq Alghubaywl , Meznah Mohammed Alanazi; Meshal Dhaifallah Qalil Alotibi , Hadi Mansour Al Yami , Hamad Hassan Alouf Alyami , Mohammed Ali Almahhan Aldwues (Migration Letters, 2022)
Background: Psoriasis is the most common T helper 1 mediated inflammatory disease, affecting more than 125 million people worldwide [1]. About 60% of psoriasis patients suffer from moderate to severe disease, i.e. more than 10% of the body surface area is covered by psoriatic plaques [2]. Objectives: To assess the prevalence of sever psoriasis among adult patient at Kingdom of Saudi Arabia 2021. Method: A retrospective case-control study was done on 50 patients who suffered from psoriasis by utilizing the charts of patients who selected randomly by accessing to management report viewer records through information technology (IT) department in Kingdom of Saudi Arabia. Results: Our cohort included 50 patients with confirmed psoriasis. Psoriasis severity was determined in 35 patients (70%). The age of our cohort ranged from 15 to 72 years with the mean of 31.4 years. The statistical analysis reported a significant correlation between age and PASI score regarding to the severity (P-value= 0.033 and 0.000 respectively), also a significant correlation between gender regarding to the severity of psoriasis (P-value= 0.000). Regarding to the severity of psoriasis among the two studied groups showed a significant correlation between the number of patients with PASI score more than 10 and the occurrence of severe psoriasis (P-value=0.001) Conclusion: the prevalence of psoriasis was higher among females. The mean age of our cases was 31.4 years. Our study depends on the PASI score to recognize the severe cases of psoriasis where we classify them according to it. Smoking and arthritis are risk factors for severe psoriasis.